Reservoir simulation and optimization of Huff-and-Puff operations in the Bakken Shale. (1st May 2015) - Sanchez-Rivera, Daniel; Mohanty, Kishore; Balhoff, Matthew
Highlights: A numerical reservoir model of the Bakken was created. Several design parameters of the Huff-and-Puff process were examined. Huff-and-Puff is most effective when natural fractures are present. CO2 costs exceed incremental oil revenue in multi-cycle treatments. Produced gas re-injection is viable from a technical and economic standpoint. Abstract: A numerical reservoir model was created to optimize Huff-and-Puff operations in the Bakken Shale. Huff-and-Puff is an enhanced oil recovery method in which a well alternates between injection, soaking, and production. Injecting CO2 (or other gases) into the formation and allowing it to "soak" re-pressurizes the reservoir and improves oil mobility, boosting production from the well. A compositional reservoir simulator (CMG GEM) was used to study various design components of the Huff-and-Puff process in order to identify the parameters with the largest impact on recovery and understand the reservoir's response to cyclical gas injection. It was found that starting Huff-and-Puff too early in the life of the well diminishes its effectiveness, and that shorter soaking periods are preferable over longer waiting times. Huff-and-Puff works best in reservoirs with highly-conductive natural fracture networks, which allow CO2 to migrate deep into the formation and mix with the reservoir fluids. Doubling the number of hydraulic fractures per stage results in considerably greater gas injection requirements without proportionally larger incremental recovery factors. Incremental recovery from CO2 Huff-and-Puff appears to be insufficient to make the process commercially feasible under current economic conditions. However, re-injecting mixtures of CO2 and produced hydrocarbon gases was shown to be technically and economically viable, and could significantly improve profit margins of Huff-and-Puff operations.